Effectiveness of subgingival irrigation and powered toothbrush as home care maintenance protocol in type 2 diabetic patients with active periodontal disease: A 4-month randomized controlled trial - Jaspreet Kaur; Vishakha Grover; Jyoti Gupta; Mili Gupta; Vinay Kapur; Manjula Mehta; Deborah M Lyle; Tanvi Samujh; Ashish Jain (Journal of Indian Society of Periodontology, 2023)
Background: There is a bidirectional link between diabetes and periodontal disease. Control of active periodontal infection is an essential requisite to maintain optimal oral and systemic health in diabetic patients. The purpose of this study was to evaluate the efficacy of subgingival irrigation and powered toothbrush as home care maintenance protocol in type 2 diabetic patients with active periodontal disease compared to routine oral hygiene. Materials and Methods: Forty (n = 40) diabetic (HbA1c >7%) patients were enrolled in this parallel, examiner-blind, interventional clinical trial. Patients were randomized into two groups: Group A (sonic toothbrush and irrigation with water twice daily) or Group B (manual toothbrush and mouth rinsing with 0.12% Chlorhexidine gluconate (CHX) twice daily)). All patients received Phase I therapybefore the start of the study. Clinical parameters (plaque index [PI], gingival index [GI], oral hygiene index [OHI], pocket depth [PD], clinical attachment level [CAL], and bleeding index [BI]) were assessed at baseline, 1, 2, and 4 months. Levels of C-reactive protein (CRP), HbA1c, and interleukin (IL)-1 β were assessed at baseline and 4 months only. Verbal and written instructions were provided to each subject specific to their intervention allocation. Descriptive, parametric, and nonparametric analyses were used where appropriate. Results: Sixteen (n = 16) patients in Group A and fifteen (n = 15) patients in Group B completed the 4-month study. Both groups showed a significant difference in BI, PD, CAL, and HbA1c from baseline to 4 months. There were no differences within groups for OHI, GI, or PI and CRP, IL-1 β. The results are based on an underpowered study due to the drop out of 9 patients reducing the number below the needed 19 patients per group based on the power analysis. Conclusion: Results from this study provide information for future studies on self-care regimens for individuals living with Type 2 diabetes.